THE RELATIONSHIP BETWEEN SALTED FISH AND HYPERTENSION IN COASTAL AREAS: A SCOPING REVIEW: Hubungan Antara Ikan Asin dan Hipertensi di Wilayah Pesisir: Sebuah Tinjauan Cakupan - Aliyah, Ira Nur; Aditya Nugraha, Bambang; Ulfah Rifa'atul Fitri, Siti (Jurnal Berkala Epidemiologi, 2026)
Background: Hypertension is a major public health issue worldwide, and its prevalence is higher in coastal areas with significant contribution from high dietary sodium such as salted fish. It is salted and dried fish that still BYs part of their daily diet in these parts, because of its very keeping-qualities and abundance. Purpose:  The purpose was to systematically map the scientific evidence on the relationship among salted fish consumption and hypertension in coastal regions. Methods: A scoping review method was used in this study based on the PRISMA-ScR guidelines. PCC were perBYed on five databases including: PubMed, Scopus, Science Direct, Cambridge Core and Google Scholar using the PCC framework with key search terms; "hypertensive patients OR hypertension patient OR hypertension sufferer" AND "salted fish OR saltwater fish" AND "coastal area". Articles were selected through strict inclusion and exclusion criteria and appraised using the Joanna Briggs Institute (JBI) guidelines. Results: A total of 376,619 articles were initially identified. After removing 75,312 duplicates, title and abstract screening excluded 330,997 articles, leaving 43 articles for full-text review. Of that 33 articles were eliminated because they did not meet methodological feasibility, and finally 10 articles with a JBI quality assessment score of ≥75% were declared eligible. Most studies reported a significant association among salted fish consumption and the incidence of hypertension, primarily based on observational study designs. The only one that did not report significant associations was a study by Williams et al. Conclusion: High intake of salted fish is significantly associated with an increased risk of hypertension among coastal populations, that may inBY on culturally appropriate interventions and community-based health promotion.